PROMOTING SUGAR INDUSTRY TO COPE WITH FUTURE CHALLENGES IN SRI LANKA: A CONSTRAINT ANALYSIS IN SEVANAGALA SUGAR FACTORY AREA - Samaraweera, Ganganee Chandima (Journal of Sugarcane Research, 2020)
Sri Lanka’s sugar sector stands in a critical stage and it fulfils only 10% of the local requirement. Sugar accounts for a quarter of the value of all food imports in Sri Lanka. The present study conducted in a sugar factory in Sri Lanka with 40 respondents (both (growers and settlers) showed that 20% of the farmers abandoned sugarcane cultivation and shifted to paddy, cowpea, coconut and maize. The major problems as stated by the farmers were absence of proper subsidy scheme, lack of efficient grading system, high transport losses (15%), comparatively lower profit gain (23%), availability of only low sugar variety (Co 775), lack of extension service and irrigation, political problems, etc. Majority of the farmers (87%) perceived the sugar factory as inefficient. Though 57% of farmers cultivate ugarcane under irrigation, there was no drastic yield difference between irrigated and rain fed systems. Twenty percent of the farmers use seed ane as planting material while 80% use ratoon due to low average cost resulting in low yield.The study recommends implementing sugar policyby controlling sugar imports to protect local producer, promoting extension service, introducing high sugar content varieties such as SL 83062 and genetically improved varieties, introducing an efficient subsidy scheme, and grading system to face the challenges ahead.